Framework for Sustainable Village Tourism Development: A Feasibility Study in South Sulawesi - Darwis, Darwis; Agus, Agus; Saleh, Armin (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The development of tourism in the tourism industry requires special attention for regional development so that clear policies are needed. Although general attributes or instructions in tourist attractions have existed, they require adjustments in rural areas. This study aims to contribute to the planning and management of sustainable tourism destinations and offer a deeper understanding. This study uses a qualitative approach. Observations and interviews were conducted as data collection techniques. The results of the study indicate the importance of integrating local culture and traditions in tourism development, as well as adjusting management strategies to global trends and local contexts. In addition, sustainable rural tourism requires a balanced approach, effective governance, strategic planning, and active participation of local communities are essential to creating a resilient tourism system. Therefore, a comprehensive framework for evaluating rural tourism destinations can be applied, effective governance, strategic planning, and collaboration between stakeholders including government agencies, the private sector, and local communities are essential in achieving sustainable tourism outcomes.